Analisis Kebutuhan Pengembangan Media Puzzle Berbasis Pembelajaran Berdiferensiasi Pada Pembelajaran IPA Kelas V Sekolah Dasar - Dwi Ummu Aulia; Firmanul Catur Wibowo; Otib Satibi Hidayat (Cetta: Jurnal Ilmu Pendidikan, 2026)
The implementation of the Kurikulum Merdeka (Independent Curriculum) encourages teachers to adopt differentiated instruction that accommodates the diverse characteristics of students. However, science instruction regarding food chains in elementary schools still faces a lack of learning media that supports differentiated instruction. This study aims to analyze the need for developing a differentiated-instruction-based puzzle medium for the food chain topic in Grade 5 elementary school, serving as the basis for formulating the medium's specifications. This study constitutes a preliminary study within the "Analysis" phase of the ADDIE development model, employing a quantitative descriptive approach. It was conducted at SDN Joglo 05, West Jakarta, involving 28 students from class VC as respondents. Data were collected using a needs analysis questionnaire comprising 25 statements across five indicators: student characteristics, the state of science instruction, the need for puzzle media, differentiation within the media, and learning outcomes. The data were analyzed using descriptive statistics, specifically mean scores and percentages. The results indicate that the need for puzzle media (92.6%), differentiation within the media (90.2%), student characteristics (85.6%), and learning outcomes (89.4%) fell into the "very high" category, whereas the state of science instruction fell into the "moderate" category (62.4%). These findings reveal a gap between the students' high need for differentiated learning media and the current state of science instruction. The results of this needs analysis serve as an empirical basis for formulating the specifications of the differentiated-instruction-based puzzle medium to be developed during the "Design" phase of the ADDIE model.